Do comorbid symptoms discriminate between autism spectrum disorder, ADHD and nonverbal learning disability?. (July 2022) - Mammarella, Irene C.; Cardillo, Ramona; Semrud-Clikeman, Margaret
Abstract: Characterizing the functioning of individuals with neurodevelopmental disorders is crucial to their diagnosis. Research has found that children with different neurodevelopmental disorders, including autism spectrum disorders (ASD), attention deficit and hyperactivity disorder (ADHD), and nonverbal learning disability (NLD), may have comorbid symptoms of anxiety and depression, and problems with pragmatic language. The main aim of the present study was to identify any differences in the above-mentioned comorbid symptoms associated with these clinical profiles. A second aim was to establish how well signs of pragmatic language difficulties could discriminate between the three clinical profiles, in terms of their diagnostic power. For this purpose, 107 participants from 8 to 16 years old with a diagnosis of ASD, ADHD or NLD were compared with a group of typically-developing children. Self-reports on symptoms of anxiety and depression, and parents' reports on social and communication problems were analyzed. Our findings confirmed that symptoms of anxiety and depression, and problems with pragmatic language are associated with different neurodevelopmental disorders, but not in the same way. In terms of diagnostic power, we found that pragmatic language difficulties clearly discriminated children with ASD, ADHD or NLD from typically-developing children. Importantly, pragmatic language difficulties also discriminated adequately between ASD and NLD. Our findings are discussed in terms of the value of considering comorbid symptoms to obtain a more accurate diagnosis of neurodevelopmental disorders. Highlights: Comorbid symptoms of anxiety, depression and pragmatics of language in children with ASD, ADHD and NLD were studied. Difficulties with pragmatic language discriminated the considered disorders (i.e., ASD, ADHD, NLD) from typical development. Further evidence to the hypothesis that NLD can be considered as a distinct profile was added.